Short-Term Supplementation of Dietary Arginine and Citrulline Modulates Gilthead Seabream (Sparus aurata) Immune Status - Ramos-Pinto, Lourenço; Azeredo, Rita; Silva, Carlota; Conceição, Luís E. C.; Dias, Jorge; Montero, Daniel; Torrecillas, Silvia; Silva, Tomé S.; Costas, Benjamin (Frontiers in Immunology, 2020)
Several amino acids (AA) are known to regulate key metabolic pathways that are crucial for immune responses. In particular, arginine (ARG) has important roles regarding immune modulation since it is required for macrophage responses and lymphocyte development. Moreover, citrulline (CIT), ARG precursor, was reported as an alternative for improving macrophage function in mammals. This study aimed to explore the effects of dietary ARG and CIT supplementation on the gilthead seabream immune status. Triplicate groups of fish (23.1±0.4 g) were either fed a control diet (CTRL) with a balanced AA profile, or the CTRL diet supplemented with graded levels of ARG or CIT (i.e. 0.5% and 1% of feed; ARG1, CIT1, ARG2 and CIT2, respectively). After 2 and 4 weeks of feeding, fish were euthanized and blood was collected for blood smears, plasma for humoral immune parameters and shotgun proteomics, and head-kidney tissue for the measurement of health-related transcripts. The bactericidal activity increased in fish fed the highest supplementation level of both AAs after 4-weeks. Peripheral monocyte numbers correlated positively with NO. A total of 94 proteins were identified in the plasma. Among them, components of the complement system, apolipoproteins, as well as some glycoproteins were found to be highly abundant. After performing a PLS of the expressed proteins, differences between the two sampling points were observed. In this regard, component 1 (61%) was correlated with the effect of sampling time, whereas component 2 (18%) seemed associated to individual variability within diet. Fish fed ARG2 and CIT2 at 4 weeks were more distant than fish fed all dietary treatments at 2-weeks and fish fed the CTRL diet at 4-weeks. Therefore, data suggest that the modulatory effects of AA supplementation at the proteome level were more effective after 4-weeks of feeding and at the higher inclusion level (i.e. 1% of feed). The csfr1 receptor tended to be up-regulated at the final sampling point regardless of diets. Data from this study point to an immunostimulatory effect of dietary ARG or CIT supplementation after 4-weeks of feeding, particularly when supplemented at a 1% inclusion level.